Pig [videorecording (DVD)] - Sarnoski, Michael; Sarnoski, Michael; Cage, Nicolas, 1965-; Cage, Nicolas, 1965-; Wolff, Alex, 1997-; Arkin, Adam (Decal, 2021)
A truffle hunter returns home to Portland, Oregon to find his beloved foraging pig who has been kidnapped.